2018
DOI: 10.1177/1129729818804997
|View full text |Cite
|
Sign up to set email alerts
|

Hand motion analysis for assessment of nursing competence in ultrasound-guided peripheral intravenous catheter placement

Abstract: Introduction: Objective measures such as hand motion analysis are needed to assess competency in technical skills, including ultrasound-guided procedures. Ultrasound-guided peripheral intravenous catheter placement has many potential benefits and is a viable skill for nurses to learn. The objective of this study was to demonstrate the feasibility and validity of hand motion analysis for assessment of nursing competence in ultrasound-guided peripheral intravenous placement. Methods: We conducted a prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Their lower overall success rate may be because their training program only included three proctored attempts, and data were only collected for the first 4 months after training. 8 While acceptable guidelines for success rates are not well known, this study shows that after 10 proctored encounters, reasonably high success rates were achieved and remained stable with further experience.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Their lower overall success rate may be because their training program only included three proctored attempts, and data were only collected for the first 4 months after training. 8 While acceptable guidelines for success rates are not well known, this study shows that after 10 proctored encounters, reasonably high success rates were achieved and remained stable with further experience.…”
Section: Discussionmentioning
confidence: 57%
“…These data are consistent with prior data collected at the same institution in 2018 that showed a first-attempt success rate of 68% and a more recent randomized control study in 2019, which showed an overall success rate of 85.4%. 11,1 A recent study of pediatric emergency nurses by Good et al 8 found an overall success rate of 60.5%. Their lower overall success rate may be because their training program only included three proctored attempts, and data were only collected for the first 4 months after training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the living subjects were healthy persons ( n = 2). The phantoms used in studies were commercially available ( n = 10) [ 13 , 23 , 34 , 35 , 38 , 40 , 44 47 ], homemade ( n = 5) [ 26 , 37 , 39 , 48 , 49 ], or a mixture of both types of phantoms [ 50 ]. One study did not specify the type of phantom they used [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…14 Because this needle-steering process requires complex skills and clinical experience, ultrasound guidance has been proposed to improve peripheral intravenous catheter (PIVC) placement success rates in patients with difficult venous access. [15][16][17] However, cannulation into smaller veins remains difficult even with the use of ultrasound-guided cannulation. In an observational study using ultrasound, the success rate was 56% (95% confidence interval (CI) ¼ 40% to 71%) for a vein diameter < 0.3 cm and 92% (95% CI ¼ 62% to 100%) for a diameter > 0.6 cm.…”
Section: Introductionmentioning
confidence: 99%